Analisis Pola Perilaku Pembelian Impulsif Generasi Z di Pontianak pada Platform Social Commerce: SOR Theory - Lang, Ratnawati (Universitas Hamzanwadi, 2024)
This study aims to explore the influence of Visual Content, Online Reviews, and Social Media Influencers on Positive Emotions and Impulse Buying on social commerce platforms among Generation Z. The methodology employed in this research is a quantitative survey involving a sample of 160 respondents consisting of students in Pontianak. Data were collected using a questionnaire with closed-ended questions and analyzed using path analysis techniques to test the proposed hypotheses. The findings reveal that Online Reviews and Social Media Influencers significantly impact Positive Emotions and Impulse Buying, while Visual Content does not show a significant influence. The study also found that Positive Emotions contribute to increased Impulse Buying. The implications of this research provide insights for marketers in designing more effective marketing strategies in the digital age, emphasizing the importance of online reviews and the role of influencers in influencing consumer buying behavior. The results of this study are expected to serve as a reference for future research in consumer behavior and digital marketing.